Ediacaran diversity in space and time - Selly, Tara; Schiffbauer, James D.; Laflamme, Marc; Warren, Lucas V. [UNESP]; Liu, Alexander G. (Cambridge University Press (CUP), 2024)
The Ediacaran Subcommission of the International Commission on Stratigraphy is diligently working toward the goal of subdividing the Ediacaran Period into precise and useful chronostratigraphic units. As emphasized by Xiao and colleagues in 2016, one of the most effective tools in this endeavor will be the use of index fossils. Our special issue serves as a presentation of ongoing research efforts aimed at advancing this task and contains explorations into taxonomy, taphonomy, and the diversity of life during the Ediacaran Period.